Ảnh hưởng của đạo đức Nho giáo đối với gia đình Việt Nam truyền thống - Trần, Thị Thơm (Tạp chí Giáo dục, 2024)
Confucianism was introduced into Vietnam during the period of Chinese domination and had a profound influence on all aspects of Vietnamese social life. In particular, Confucian ethical concepts had a clear influence on traditional Vietnamese families. However, traditional Vietnamese families did not mechanically absorb Confucian ethical ideas but adapted them to suit the socio-economic and cultural conditions of Vietnam. This article explores the influence of Confucian ethics on traditional Vietnamese families, thereby affirming the necessity of promoting the positive influences of Confucian ethics on traditional Vietnamese families in building Vietnamese families today. Inheriting the positive values of traditional Vietnamese family ethics under the influence of Confucianism in building Vietnamese families today is very necessary, but the inheritance needs to be done flexibly to be suitable for socio-economic characteristics and the characteristics of Vietnamese families today.